The Subaltern Voice in A Thousand Splendid Suns by Khaled Khosseini - Soraya, Soraya (Bina Nusantara University, 2015)
Life in Afghanistan puts female as the second sex and the victims of patriarchy. In the eye of Orientalism, women are the east. Thus, they can be colonized and suppressed (the subaltern). This study was designed to answer the question how was the voice of the subaltern being represented by the characters in the novel A Thousand Splendid Suns by Khaled Khosseini. Library research was applied in this study. Data were Â analyzed using postcolonial theory, specifically from Gayatri Spivak. The conclusion presents that both characters, Mariam and Laila is the representation of the subaltern who created voice to fight against the oppression. Between Mariam, the symbol of traditional woman, and Laila, the symbol of modern woman, only Laila who can reach the freedom. However, it is impossible to achieve without the courage and sacrifice of MariamÂ